Students’ Perception in Learning the Course Mathematics in the Modern World: A Qualitative Study - Barete, Melvin; Taja-on, Evan (East Asian Journal of Multidisciplinary Research, 2024)
Mathematics fosters analytical thinking, problem-solving, and logical reasoning, essential for academic success and daily decisions. The course "Mathematics in the Modern World" aims to make mathematics more relatable by using real-life scenarios, countering its abstract and difficult perception. This study used a hermeneutic phenomenological narrative inquiry to explore the experiences and perceptions of six college students. This study used a hermeneutic phenomenological narrative inquiry to explore the experiences and perceptions of six college students. The inquiry focuses on individuals' accounts to comprehensively explore their lived experiences and the meanings they construct around learning mathematics. Data, gathered through in-depth interviews and a validated questionnaire, revealed that students view mathematics as practical and essential. Real-world applications and positive learning experiences enhance engagement, confidence, and motivation. Supportive teaching practices and practical examples foster a deeper understanding, leading to a more effective and satisfying educational experience.